Pengaruh Gaya Hidup Digital dan Persepsi Kemudahan terhadap Penggunaan E-Wallet pada Generasi Z di Provinsi Bali - I Putu Sendy Wiranata; I Komang Putra; I Ketut Darma (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study examines the influence of digital lifestyle and perceived ease of use on E-wallet usage among Generation Z in Bali Province. The study involved 100 Gen Z respondents who had used E-wallets within the last three months. A quantitative approach was applied using multiple linear regression analysis, supported by classical assumption tests, as well as F-test and t-test. The results reveal that both digital lifestyle and perceived ease of use significantly affect E-wallet usage, both partially and simultaneously. These findings indicate that higher digital engagement and greater perceived ease of use contribute to increased adoption of E-wallet services among Generation Z. The study emphasizes the importance of improving user-friendly features and digital integration to support financial technology adoption. Therefore, E-wallet providers are encouraged to continue innovating, enhance usability, and expand promotional efforts and partnerships to increase usage among Generation Z in Bali.